PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN LAPTOP MEREK ASUS PADA TOKO PROMEDIA.COM PEKANBARU - ????????????????????????, ????????????????????????????; ????????????????????????????, ???????????????? (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how the influence of product quality (performance (performance), additional features (features), reliability (reability), conformance with specifications (conformance), endurance (durability), serviceability, aesthetic (aesthetic), and perceived quality (perceived quality) and brand trust (Brand Competence), Brand Reputation, Company Reputation, Liking For Brand to purchasing decisions (perceived needs, activities before buying, time behavior buy and post-purchase behavior) Asus brand laptops on the Promedia.com Pekanbaru Store. The population in this study were consumers who bought the Asus brand laptop at Promedia.com Pekanbaru Store. Sampling in this study is 91 samples using Slovin formula. The data collection of this research is in the form of primary data by spreading research instruments and secondary data in the form of company archives, data analysis in this study using multiple regression, partial test (t test), determination test (r test) and simultaneous test (f test) with the help of the SPSS program. The results in this study indicate that the variable product quality and brand trust partially (t test) affect the purchase decision of the Asus brand laptop at Promedia.com Pekanbaru Store. Simultaneous results (f test) indicate a significant influence on the purchase decision of the Asus brand laptop at Promedia.com Pekanbaru Store.Keywords: Product Quality, Brand Trust, Purchasing Decision